Ultrasound features versus Magnetic resonance imaging features for diagnosis and prediction of morbidity of placenta accreta in pregnant women between 34 and 37 weeks of gestation - Sherif Omar Abd Al Rafee; Sherihan Fakhry Dakhly (2021)
(3JYO GdeTjeI GdedJUbI HLOGQ GdQMe hGMOI ef Cge CSHGH GdhaGI hGdeVGYaGJ ddSjOGJ CKfGA h HYO GdhdGOI(B. (3agi JYO CTgQ CSHGH haGg GdGe HYO GdhdGOI ai GdOhd GdeJbOeI(B. (3YfOeG Jchf GdeTjeI edJUbI heNJQbI dLOGQ GdQMe hjUYH aUdgG efg HYO GdhdGOI jMOK fRja MGO HYO GdhdGOI eeG bO jMJGL dfbd GdOe HeTJbGJg, ceG bO jDOi Pdc Gdi MOhK eVGYaGJ LSjeI cEUGHI CMTGA GdHWf ChGdeKGfI GdHhdjI Gh GdMGdH HGdEPGA ai MGdI GdeTjeI GdeNJQbI hbO JMJGL GdeQjVI ddMLR HGdYfGjI GdeQcRI deJGHYI GdhXGFa GdMjhjI hbO jfJgi Pdc cdg HGdhaGg(B. (3JHjf ef GdOQGSGJ GdeJYOOI Cf fSHI MOhKGdeTjeI GdedJUbI Gh GdeNJQbI dLOGQ GdQMe JRjO eY RjGOI YOO GdhdGOGJ GdbjUQjI NGUI ai MGdI hLhO GdeTjeI GdeJbOeI GdJi JUd Ch JZWi Yfb GdQMe (B. (3JgOa OQGSJfG Gdi EjLGO hSjdI BefI haYGdI hObjbI dJTNjU GdeTjeI GdeNJQbI bHd GdhdGOI dYed GdGSJYOGOGJ hCNP GdGMJjGWGJ GddGReI bHd GdhdGOI ddMO ef fSHI MOhK GdeVGYaGJ HYO GdhdGOI GdJi bO JUd Gdi MO GdhaGg(B.s
Thesis (Ph.D)-Cairo University,2021
Bibliography: p. 107-123.
Keywords: Obstetrics and Gynecology; Ultrasound